Pengaruh Struktur Modal Terhadap Sisa Hasil Usaha (SHU) Melalui Volume Usaha Pada Koperasi Simpan Pinjam Di Indonesia : Periode Sebelum dan Saat Pandemi Corona Virus Disease 2019 - Patra Anggana, Reza; Purnamawati, Ami; Wahyudin, Wahyudin (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The purpose of this study was to test and analyze the effect of own capital and loan capital on business volume both partially and simultaneously. To test and analyze the effect of own capital, outside capital, and business volume on the net profit (SHU) both partially and simultaneously. To test and analyze the effect of own capital and outside capital partially on net profit (SHU) with business volume as an intervening variable. The analysis technique used in this research is quantitative data analysis, namely testing and analyzing data with numerical calculations and then drawing conclusions from these tests with panel data regression model analysis techniques. The population of this study is all active Savings and Loan Cooperatives and reports the RAT to the Ministry of Cooperatives and SMEs and the data is presented in aggregate per province in 34 provinces in Indonesia with the research period before the covid-19 pandemic (2017-2019) and during the covid-19 pandemic (2020-2022). Based on the research results, it can be concluded that own capital and external capital partially and simultaneously have a significant effect on business volume both before and during the covid-19 pandemic. Own capital, external capital, and business volume partially and simultaneously have a significant effect on net profit (SHU) before and during the covid-19 pandemic. Business volume is not an intervening variable between the variables of own capital and loan capital on net profit (SHU) before the covid-19 pandemic. Business volume is an intervening variable between the variables of own capital and loan capital on net profit (SHU) during the covid-19 pandemic.